The image of «home» in N.A. Baykov’s short story collection «By the Fire» - L. Dorofeeva; L. Gu (Язык и текст)
Home is a recurring theme in the literature of the Russian diaspora of the first wave, reflecting the state of being of Russians in a “foreign” space. The image of home in the works of N. Baykov acquires its unique features associated with both the peculiarities of his biography and personality, and with the specifics of his work. The article examines the semantics of the space of home based on several stories from N. Baykov’s collection “By the Fire”. The opposition of “one’s own”/“foreign” space and the specifics of their interaction as “home” and “homelessness” are revealed. The key theme in the stories “New Year’s Eve”, “On the Deck of a Steamship” and “The Secret of a Bottle” is emigration and the image of Russia. The authors come to the conclusion that the image of home is realized at the levels of external and internal spaces, the semantics of which is determined by the category of freedom.